Evaluation of Outcomes in Patients Receiving Amantadine to Improve Alertness After Traumatic Brain Injury. (October 2021) - Hadgu, Rim M.; Borghol, Amne; Gillard, Christopher; Wilson, Candice; Elqess Mossa, Suzan; McKay, Megan; Jastram, Charles; Onor, Ifeanyi O.
Background: Amantadine has been used off-label to improve alertness after traumatic brain injury (TBI). The goal of this study is to assess the mean change at 72 hours and in course of therapy (COT) Glasgow Coma Scale (GCS) score after amantadine initiation and to correlate the change in GCS score with participation in physical therapy (PT) and occupational therapy (OT) among patients with TBI receiving amantadine during the first hospitalization.Methods: This single-center, retrospective, cohort study included patients ≥18 years old hospitalized for a TBI from August 2012 to February 2018 and received ≥1 dose of amantadine to increase alertness. The primary endpoint is the mean change in 72-hour GCS score after amantadine initiation. The secondary endpoint is the mean change in COT GCS score after amantadine initiation and the correlation between the change in GCS score and percent PT and OT participation at 72 hours and during the COT.Results: Seventy-nine patients were included. The mean age of patients was 41 years, and 79.8% of the patients were men. The mean change in 72-hour GCS score was +0.75 (95% confidence interval [CI] = 0.09-1.42, P = .027), and the mean change in COT GCS score was +2.29 (95% CI = 1.68-2.90, P < .001). There was no significant correlation between the increase in GCS score and percent PT/OT session participation at 72 hours and during the COT, r = −0.15 ( P = .24) and r = −0.02 ( P = .74), respectively. The percent PT/OT session participation at 72-hour post-amantadine initiation was 61.3% compared with 65.9% during the COT.Conclusion: There were small but statistically significant increases in the mean change at 72 hours and in COT GCS score; however, they were not correlated with percent PT/OT participation. Other studies are needed to determine the appropriate time and GCS score to initiate amantadine along with the optimal dose in the inpatient setting.